Analisis Kemampuan Guru Pendidikan Agama Islam Dalam Menyusun Soal HOTS - Ifadah, Khusnul; Pristiwiyanto, Pristiwiyanto; Mustain, Mustain (Program Studi Pendidikan Agama Islam, 2023)
The learning process at school trains and familiarizes students with interactions with society, not just involving them in the complexity of problems that exist in society. Students must be able to take on roles no matter how small according to their respective skills. Apart from that, the problem is the complexity of the community situation itself. From this situation, a PAI teacher must be able to make students able to process information, make generalizations, solve problems, connect causality, and relate the concepts of religious sciences to everyday life for themselves and society. The focus of this research is what is the ability of PAI teachers to compose HOTS questions at AL Azhar Menganti Vocational School? and What factors influence the teacher's ability to compose HOTS questions at AL Azhar Menganti Vocational School. This research uses a descriptive qualitative type through interviews, observation and documentation methods. The results of this research are that the ability of PAI subject teachers at AL Azhar Menganti Vocational School in making LOTS questions is categorized as capable because LOTS questions are easier for teachers to make and done by students and in daily learning. Factors that influence the teacher's ability to compose HOTS questions at AL Azhar Menganti Vocational School are the teacher's limited time in creating HOTS questions, not understanding how to find and match KKOs for the questions being created, and inappropriate selection of KDs and minimal socialization regarding the preparation of HOTS questions.